Histone H3 K4 trimethylation occurs mainly at the origins of polycistronic transcription in the genome of Leishmania infantum promastigotes and intracellular amastigotes - Aurora Diotallevi; Stefano Amatori; Giuseppe Persico; Gloria Buffi; Enrica Sordini; Marco Giorgio; Mirco Fanelli; Luca Galluzzi (BMC Genomics)
Abstract Background Trypanosomatids include the genera Trypanosoma and Leishmania, which are the etiological agents of important human diseases. These pathogens present unique mechanisms of gene expression characterized by functionally unrelated genes positioned in tandem and organized into polycistronic transcription units transcribed in a large pre-mRNA by RNA Polymerase II. Since most of the genome is constitutively transcribed, gene expression is primarily controlled by post-transcriptional processes. As in other organisms, histones in trypanosomatids contain a considerable number of post-translational modifications, highly conserved across evolution, such as the acetylation and methylation of some lysines on histone H3 and H4. These modifications have been mainly studied in Trypanosoma spp. The aim of this work was to elucidate the distribution of histone H3 lysine 4 trimethylation (H3K4me3) over the chromatin landscape of Leishmania infantum, the causative agent of canine and human leishmaniasis in the Mediterranean region. To this end, we investigated by chromatin immunoprecipitation (ChIP)-sequencing either the promastigotes (the flagellated motile form) and the amastigotes (the intracellular form) in an in vitro infection model. Results The chromatin was prepared from THP-1 cells non infected, THP-1 cells infected with L. infantum MHOM/FR/78/LEM75, and THP-1 cells non infected and mixed with L. infantum MHOM/FR/78/LEM75 promastigotes. ChIP was conducted using anti-H3K4me3 or anti-H3K27me3 antibodies and ChIP-seq was performed on an Ion S5 sequencer. We showed that histone H3K4me3 is mainly enriched at transcription start sites (67%) or internally within the polycistronic transcription units (30%), with no differences between L. infantum promastigotes and amastigotes. Moreover, the enriched regions co-localize with another hallmark of transcriptional activation (histone H3 acetylation) in L. major, a species characterized by a high degree of synteny with L. infantum. Conclusions These findings expand our knowledge of the epigenomics of Leishmania parasites, focusing on epigenetic markers associated with transcription in L. infantum, and will contribute to elucidate the transcriptional mechanisms in these pathogens.